Hidden Obesity - Kalra , Sanjay; Arora, Saurabh; Kapoor, Nitin (Journal of the Pakistan Medical Association, 2023)
This communication proposes the term “hidden obesity” to describe normal weight obesity, or increased adiposity without a corresponding increase in body mass index. It uses the concept of hidden hunger to craft semantics which will generate greater attention to this condition from all stake-holders, including policymakers and planners. The article describes simple tools which can be used to suspect and confirm the diagnosis of hidden obesity. This phenotype is very commonly seen in the south Asian population. Keywords: Barophenotypic characterization, normal weight obesity, obesity, overweight, hidden hunger